2006
DOI: 10.1038/nrm2003
|View full text |Cite
|
Sign up to set email alerts
|

SUN-domain proteins: 'Velcro' that links the nucleoskeleton to the cytoskeleton

Abstract: The novel SUN-domain family of nuclear envelope proteins interacts with various KASH-domain partners to form SUN-domain-dependent 'bridges' across the inner and outer nuclear membranes. These bridges physically connect the nucleus to every major component of the cytoskeleton. SUN-domain proteins have diverse roles in nuclear positioning, centrosome localization, germ-cell development, telomere positioning and apoptosis. By serving both as mechanical adaptors and nuclear envelope receptors, we propose that SUN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
221
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(226 citation statements)
references
References 56 publications
1
221
0
1
Order By: Relevance
“…2; for review see 6,[13][14][15]. In general, SUN proteins contain a conserved SUN domain at their C-termini and at least one transmembrane domain.…”
Section: Kash and Sun Proteins Bridge The Nuclear Envelopementioning
confidence: 99%
See 1 more Smart Citation
“…2; for review see 6,[13][14][15]. In general, SUN proteins contain a conserved SUN domain at their C-termini and at least one transmembrane domain.…”
Section: Kash and Sun Proteins Bridge The Nuclear Envelopementioning
confidence: 99%
“…2; for review see ref. 6,[13][14][15]. The nuclear envelope bridging model has been refined by four groups who have each concluded that SUN proteins reside in the INM where they function to target and retain KASH proteins to the ONM through a direct interaction.…”
Section: Kash and Sun Proteins Bridge The Nuclear Envelopementioning
confidence: 99%
“…Mps3 contains a SUN domain (Sad1-Unc84) within its inter-membrane region which allows it to connect the SPB with the nuclear envelope. 25,26 Mps3 is the only SUN domain protein in budding yeast, while at least two SUN domain proteins exist in C. elegans and Drosophlila, and mammalian cells have four SUN domain proteins. In the latter case, SUN domains are known to interact with the KASH domain of outer nuclear membrane proteins, such as Nesprin, bridging the nuclear envelope to the actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…At the cell surface, IF interact with desmosomes, hemidesmosomes, focal adhesions and the extracellular matrix via a variety of linker proteins [3][4][5]. There is also evidence that IF associate with factors on the outer nuclear membrane which, in turn, connect to components of the nuclear lamina [4,6]. These observations suggest that IF form a continuous network of nanofibrils along which signals from the cell's exterior can be transmitted to the nuclear surface and the nucleoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive distribution of IF provides an enormous surface area which can act as a scaffold for the binding of numerous types of regulatory and signaling molecules [8,9]. The IF system has also been shown to associate with membranous organelles such as mitochondria, the Golgi apparatus and vesicles, as well as with other cytoskeletal components such as actin filaments, microtubules, and their associated molecular motors [4,6,10]. Thus the IF system is positioned to perform significant roles in the internal organization and positioning of organelles and other cytoplasmic components.…”
Section: Introductionmentioning
confidence: 99%